The Online Mass Media and Organic Image Formation: a Case Study of The Bintan Destination During The Post Covid-19 Pandemic Recovery Period - Taufiqqurrachman Taufiqqurrachman; Nanik Rahmawati; Teguh Setiandika Igiasi (Relevance: Journal of Management and Business, 2023)
Online mass media is a source of information for tourists, which impacts the formation of their destination image. This article is scientific research aimed at identifying the formation of the image of the Bintan destination through two elements: the two online mass media (Kompas and Detik.com) and tourists during the post-COVID-19 pandemic recovery period. Thematic analysis techniques were applied in this study to identify image formation by producing tourism news content originating from those media. Meanwhile, the image formation of the selected tourist was identified through Z.E.M.T. interviews. Data collected from those media and informants was analyzed using the Atlas-TI application. The results of this study show several findings. First, the post-Covid-19 recovery period has impacted image formation by those media. This is shown by the dominant appearance of the theme facility of tourism in the data, especially in the news on Detik.com. Second, the congruence between the two elements (Kompas and Detik.com and tourists) in terms of their emphasis on the theme of natural attractions and tourist activities. Theoretical and practical implications, as well as some suggestions for future research, are discussed and proposed in this article.